2019
DOI: 10.15809/irriga.2019v24n4p890-899
|View full text |Cite
|
Sign up to set email alerts
|

COMPORTAMENTO FISIOLÓGICO DE MUDAS DE CAFEEIRO ARÁBICA (cv. OBATÃ E CATUCAÍ) SUBMETIDAS À DEFICIÊNCIA HÍDRICA

Abstract: COMPORTAMENTO FISIOLÓGICO DE MUDAS DE CAFEEIRO ARÁBICA (cv. OBATÃ E CATUCAÍ) SUBMETIDAS À DEFICIÊNCIA HÍDRICA     ENRIQUE ALONSO ZUÑIGA1*; LUZ MARIA RUIZ MACHUCA1; OSVALDIR FELICIANO DOS SANTOS1; MARA LÚCIA CRUZ DE SOUZA1; DARIANE PRISCILA FRANCO DE OLIVEIRA1 E FERNANDO BROETTO 2   1Departamento de Engenharia Rural, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista (UNESP) Campus de Botucatu. Fazenda Experimental Lageado, Avenida Universitária, n° 3780, Altos do Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies evaluating plants in situations of water deficit have observed that the chlorophyll content increased with a decrease in the volumetric water content in the soil [50,51]. Conversely, [52] observed that coffee plants grown in winter and growing under water stress showed no changes in chlorophyll content.…”
Section: Dry Seasonmentioning
confidence: 99%
“…Some studies evaluating plants in situations of water deficit have observed that the chlorophyll content increased with a decrease in the volumetric water content in the soil [50,51]. Conversely, [52] observed that coffee plants grown in winter and growing under water stress showed no changes in chlorophyll content.…”
Section: Dry Seasonmentioning
confidence: 99%